1994
DOI: 10.1128/aac.38.2.353
|View full text |Cite
|
Sign up to set email alerts
|

beta-Lactam resistance of motile Aeromonas isolates from clinical and environmental sources

Abstract: The MICs of various beta-lactams for 182 isolates of Aeromonas species, i.e., A. hydrophila (n = 101), A. sobria (n = 69), and A. caviae (n = 12), from clinical and environmental sources were determined by an agar dilution technique. All strains were resistant to ampicillin and susceptible to aztreonam. A. sobria and A. caviae demonstrated lower resistance rates than A. hydrophila. Penicillin-hydrolyzing beta-lactamases were detected in all strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…The large spectra of resistance to β-lactam antibiotics, the resistance to imipenem (a drug highly stable to serine-β-lactamases), as well as the inefficiency of clavulanic acid and sulbactam to inhibit Aeromonas β-lactamases, corroborate previous results indicating the chromosomally mediated production of metallo-β-lactamases by these bacteria (21,25). Furthermore, beyond the penicillins and first generation cephalosporins, some isolates (18.5%) showed resistance to several new extended-spectrum cephalosporins, and one isolate of A. hydrophila exhibited resistance to aztreonam and all the penicillins and cephalosponins.…”
Section: Resultssupporting
confidence: 84%
“…The large spectra of resistance to β-lactam antibiotics, the resistance to imipenem (a drug highly stable to serine-β-lactamases), as well as the inefficiency of clavulanic acid and sulbactam to inhibit Aeromonas β-lactamases, corroborate previous results indicating the chromosomally mediated production of metallo-β-lactamases by these bacteria (21,25). Furthermore, beyond the penicillins and first generation cephalosporins, some isolates (18.5%) showed resistance to several new extended-spectrum cephalosporins, and one isolate of A. hydrophila exhibited resistance to aztreonam and all the penicillins and cephalosponins.…”
Section: Resultssupporting
confidence: 84%
“…Remarkably in this work, imipenem resistance was observed in three isolates of Aeromonas (1 A. aquariorum, 1 A. veronii and 1 A. jandaei). Other studies also reported the incidence of strains resistant to this antibiotic [24,25]. Resistance to imipenem in non clinical strains supposed not subjected to selective pressure by use of such drug is a worrying trait as this is a last-resort antimicrobial agent used in the clinical environment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results obtained using commercial kits and disc diffusion technique, especially the susceptibility tests to beta lactam antibiotics shoud be verified by agar dilution technique (Schadow et al 1993;Morita et al 1994). …”
Section: Discussionmentioning
confidence: 99%